Isolation and characterization of equine peripheral blood-derived multipotent mesenchymal stromal cells - Carvalho,Armando de M. (2013)
The objective of the study was to isolate, cultivate and characterize equine peripheral blood-derived multipotent mesenchymal stromal cells (PbMSCs). Peripheral blood was collected, followed by the isolation of mononuclear cells using density gradient reagents, and the cultivation of adherent cells. Monoclonal mouse anti-horse CD13, mouse anti-horse CD44, and mouse anti-rat CD90 antibodies were used for the immunophenotypic characterization of the surface of the PbMSCs. These cells were also cultured in specific media for adipogenic and chondrogenic differentiation. There was no expression of the CD13 marker, but CD44 and CD90 were expressed in all of the passages tested. After 14 days of cell differentiation into adipocytes, lipid droplets were observed upon Oil Red O (ORO) staining. Twenty-one days after chondrogenic differentiation, the cells were stained with Alcian Blue. Although the technique for the isolation of these cells requires improvement, the present study demonstrates the partial characterization of PbMSCs, classifying them as a promising type of progenitor cells for use in equine cell therapy.